2023
DOI: 10.3390/ijerph20010855
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-Temporal Variations and Trade-Offs of Ecosystem Services in Anhui Province, China

Abstract: Research on the spatiotemporal evolution and trade-offs of ecosystem services (ESs) is important for optimizing the ecological security barrier system and promoting coordinated socio-economic development. Natural factors, e.g., climate change, and human factors, e.g., unreasonable land use, have impacted and damaged ecosystem structure and function, leading to challenges with ES trade-offs and the spatial identification of priority protected areas. Here, the spatiotemporal evolution characteristics of five ESs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…However, in general, the increase in precipitation and NDVI has offset the negative impact of highway construction on ecological risk, so ecological risk in the study area is decreasing year by year. Spatially, previous studies (Wang, 2019) and this study found that higher ESV was mainly distributed across the northeast plain and Yellow River shore with lower risk levels. The areas of lower ESV were mainly concentrated in dunes in middle and other land areas in the west with higher risk.…”
Section: Influencing Factors and Strategies Based On Spatial Correlationsupporting
confidence: 57%
“…However, in general, the increase in precipitation and NDVI has offset the negative impact of highway construction on ecological risk, so ecological risk in the study area is decreasing year by year. Spatially, previous studies (Wang, 2019) and this study found that higher ESV was mainly distributed across the northeast plain and Yellow River shore with lower risk levels. The areas of lower ESV were mainly concentrated in dunes in middle and other land areas in the west with higher risk.…”
Section: Influencing Factors and Strategies Based On Spatial Correlationsupporting
confidence: 57%
“…In fact, compared with other provincial research areas in China, the absolute value of carbon storage reduction in Liaoning Province from 2000 to 2020 was relatively small, at 0.51 Tg. During the same period, Anhui Province lost 33.84 Tg [68], Guangdong Province lost 6.53 Tg [69], and Shandong Province lost 6.57 Tg [70]. The reason for these differences may be the effective implementation of ecological protection policies in Liaoning Province.…”
Section: Influence Of Policy On Carbon Storage In Citiesmentioning
confidence: 99%
“…The runoff retention volume R f mi m 3 (P − Q p,i ) and runoff retention index R f mi (1 − Q p,i /P) represent the capacity of flood risk mitigation. With reference to the previous literature [39], this paper uses runoff retention volume as the supply of flood mitigation services. Specifically, the input parameter P s adopts the definition of a rain storm in China's meteorological standards, which is 50 mm rain within 24 h. (http://www.cma.gov.cn/2011xzt/kpbd/rainstorm/ 2018050901/201805/t20180509_468007.html, accessed on 9 February 2021).…”
Section: Methods Of Es Supply Quantification 221 Flood Mitigation Ser...mentioning
confidence: 99%
“…The capacity of the city's flood control and mitigation plays an important role in reducing urban waterlogging [38,39]. The latest version of the InVEST model added the Urban Flood Risk Mitigation model and the Urban Cooling Model, which are more suitable for finer assessment of urban ecosystem services on a smaller scale, and relevant to the ecological problems of the city's concern.…”
Section: Flood Mitigation Service Supply Quantificationmentioning
confidence: 99%